أثر الرش الورقي بالأحماض الأمينية في بعض مكونات الإنتاجية لصنف الفول الإسباني (Luz de otono) (مجلة جامعة اللاذقية- سلسلة العلوم البيولوجية, 2019)
The experiment was carried out at Hmeimim-Jableh in Lattakia government, according to the randomized complete block design (RCBD), with three replicates per treatment during the season 2018. The research aimed to study the effect of foliar spraying with different concentrations of amino acids (0.5, 1, 2.5, 5 and 10 g/L) on some plant growth and productivity characteristics in Spanish faba bean (Vicia faba L.) (Luz de otono variety) plants. So, the morphological and physiological (plant height (cm), plant leaf area (cm2/plant), leaf area index (LAI), photosynthesis rate (g/cm2/day) and crop growth rate (g/m2/day)), the productivity (the fresh pods yield and its components and the fresh and dry seeds weight) and seed total protein content (%) have been estimated. The results showed a significant difference (P